Robust envelope exchange platform for oncolytic measles virus - Neault, Serge; Bossow, Sascha; Achard, C.; Bell, J. C.; Diallo, J. S.; Leber, Mathias Felix; Ungerechts, Guy (Journal of virological methods, 2022)
The use of oncolytic viruses (OV) to precisely target and eliminate tumors (‘virotherapy’) is a rapidly evolving therapeutic approach to treating cancer. A major obstacle in virotherapy, especially for systemic administration, is the host’s immune response towards the OV. In the case of measles virus (MeV), most individuals have been immunized against this agent leading to pre-existing neutralizing antibodies that can impair OV delivery to the tumor. These antibodies predominantly target the hemagglutinin (H) and fusion (F) envelope glycoproteins displayed at the particle’s surface. Here, we introduce a novel and versatile pseudotyping platform for rapid envelope exchange of oncolytic MeV that allows for engineering of chimeric viruses invulnerable to pre-existing anti-MeV antibodies. Using this system, we have successfully exchanged the MeV F and H proteins with the glycoprotein G of vesicular stomatitis virus (VSV) and the surface proteins of Newcastle disease virus (NDV) or canine distemper virus (CDV), all of which are not endemic in the general human population. While the MeV-VSV and MeV-NDV pseudotypes were non-functional, the MeV-CDV pseudotype was successfully propagated to high-titer virus stocks. This study describes the successful generation of a robust envelope exchange platform for oncolytic MeV while also highlighting its intricate pseudotyping tolerance.
Gesehen am 22.04.2022